2020
DOI: 10.1242/jcs.235044
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-dependent trafficking and activity of GDE2, a GPI-specific phospholipase promoting neuronal differentiation

Abstract: GDE2 (also known as GDPD5) is a multispanning membrane phosphodiesterase with phospholipase D-like activity that cleaves select glycosylphosphatidylinositol (GPI)-anchored proteins and thereby promotes neuronal differentiation both in vitro and in vivo. GDE2 is a prognostic marker in neuroblastoma, while loss of GDE2 leads to progressive neurodegeneration in mice; however, its regulation remains unclear. Here, we report that, in immature neuronal cells, GDE2 undergoes constitutive endocytosis and travels back … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
(67 reference statements)
1
6
0
Order By: Relevance
“…In uninfected CAD and SH-SY5Y cells, both Rab5 and Rab11 concentrate at one perinuclear region (Fig. 7A, D, G, and K), consistent with previous observations (28,41). This concentration of membranes is dependent on the microtubule network (Fig.…”
Section: Resultssupporting
confidence: 91%
“…In uninfected CAD and SH-SY5Y cells, both Rab5 and Rab11 concentrate at one perinuclear region (Fig. 7A, D, G, and K), consistent with previous observations (28,41). This concentration of membranes is dependent on the microtubule network (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Our studies showed that BACE expression was not affected by GDE2 and RECK expression. GDE2 and RECK function on the plasma membrane and not endosomes (21,29,(40)(41)(42), and putative activation functions of RECK on aspartyl proteases such as BACE have not been reported. Accordingly, potential effects of GDE2-RECK on BACE are likely to be indirect.…”
Section: Discussionmentioning
confidence: 99%
“…S4, table S1, and data file S1). Because GDE2 function requires expression on the cell surface (26,29), these observations suggest that GDE2 trafficking and function are disrupted in neurons of patients with AD.…”
Section: Of 14mentioning
confidence: 99%
“…In contrast to control patients, we find that in motor cortex of patients with ALS, hGDE2 is no longer expressed on the cell surface but instead aberrantly accumulates within cells. Structure-function studies in heterologous cells have shown that surface expression of GDE2 is critical for its GPI-anchor cleavage function [36]. Accordingly, intracellular accumulation of hGDE2 in ALS patient samples is suggestive of a failure of GDE2 enzymatic function in ALS.…”
Section: Discussionmentioning
confidence: 99%